HAND-IN-ACTION: Pemberdayaan Pasien Carpal Tunnel Syndrome melalui Latihan Gliding Exercise - Tri, Renny; Erinda, Septi; Satria, Dava; Puspita, Dona Aliya; Elvindo, Dwi Dendy; Anggraini Br Manik, Ema; Patul Husna, Hani; Rahmadani, Karina; Nurhalizah, Nurhalizah; Merzalia, Cinta; Anzamika, Umi (Jurnal Nusantara Mengabdi, 2024)
Purpose: This study aims to explore the empowerment of Carpal Tunnel Syndrome (CTS) patients through gliding exercises, with a focus on its role in reducing symptoms and improving hand function.Methodology/approach: This counseling was carried out at the Purjaya village health post involving 20 CTS patients. A structured gliding training program was implemented, including tendon gliding and neural gliding techniques. The effectiveness of the exercise was evaluated using leaflets.Results/findings: The findings indicate that regular gliding exercises significantly reduce pain, improve hand mobility, and enhance functional use of the affected hand. Patients reported increased comfort in daily activities and reduced reliance on pain medication.Limitations: The study is limited by its sample size and duration, requiring further longitudinal research to confirm long-term benefits.Contribution: This study highlights the importance of non-invasive interventions in managing CTS, providing an effective, low-cost, and accessible rehabilitation method for patients and healthcare practitioners.